PUBLIC SPEAKING ASSISTANCE IN ORDER TO DEVELOP THE INTERESTS AND TALENTS OF STUDENTS OF THE INDONESIAN ISLAMIC STUDENT MOVEMENT, MAJAPAHIT ISLAMIC UNIVERSITY. - Wachidah, Hajar Nurma; Lailin, Moch. Ichdah Asyarin Hayau; Devi, Ratnaningrum Zusysana (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2025)
Public Speaking Training is a series of activities designed to improve one's ability to speak in public. This training is very important, especially for students, because good speaking skills will be very useful in various aspects of life, such as presenting assignments, attending seminars, or even having a career. However, many of the current Zero generation have a low level of self-confidence so they need motivation to be active in speaking, conveying aspirations, organising, especially students as the nation's successors. In this mentoring and public speaking training activity, several methods are used, namely needs mapping, material preparation, training implementation, evaluation. The result of this service is that PMII students at Majapahit Islamic University experience an increase in self-confidence, an increase in delivering messages, an increase in mastering the audience and an increase in soft skills that are more vocal and dare to express their opinions.